Curricular diversification and the validity of interculturality in the teachers of the Unidad de Gestión Educativa Local of Collao-Ilave - Pérez, Katia; Pérez, Tula; Puño, Luis; León, Lesy (Revista Innova Educación, 2019)
The research was carried out with the purpose of determining the relationship between curricular diversification and the validity of interculturality in the teachers of the UGEL Collao - Ilave, regarding the variables: curricular diversification and the validity of interculturality. Methodologically, the research is descriptive correlational type; the population is made up of 50 teachers, who were given a survey of 20 items to measure the curricular diversification variable and a questionnaire was used to measure the validity variable of interculturality. To establish the correlation between the variables of curricular diversification and the validity of interculturality, the Pearson R coefficient was used. The results of the research are the following: There is a moderate positive correlation between curricular diversification and the validity of interculturality. This conclusion is based on Pearson's statistical correlation test of R that is equal to 0.408 **; which means that the existence of a curricular diversification will have a validity of moderate interculturality; the teachers of the UGEL Ilave consider interculturality valid.
Keywords: Learning; curriculum; diversification; teaching; interculturality